Optimalisasi Layanan Disabilitas Hamzanwadi Untuk Siswa Dengan Autisme Di Sekolah Dasar: Penelitian Pengabdian Di MIS Nw Selong - Abdul Khair; Nindya Seva Kusmaningsih; Khoirun Annisah (Universitas 17 Agustus 1945 Jakarta, 2026)
The aim of this service activity is to find out steps to optimize Hamzanwadi Disability Services in supporting the development of students with autism in elementary schools. The focus of service is carried out at MIS NW Selong by involving teachers, parents and students as the main subjects. Students with autism in elementary school still face various obstacles, especially in aspects of communication, social interaction and behavior regulation. Therefore, structured and collaborative services are needed to support their learning needs. The method used in this activity is a descriptive approach with data collection techniques in the form of observation, in-depth interviews and documentation. Activities are carried out through initial assessment stages, teacher training, preparation of Individual Learning Programs (PPI), as well as assistance with the implementation of services in the classroom. The results of the service show that the optimization of Hamzanwadi disability services is effective and sustainable in increasing student involvement in the learning process. Collaboration between teachers and parents in implementing appropriate learning strategies can increase student motivation and learning responses. Apart from that, implementing a structured, consistent and supportive learning environment is an important factor in supporting student development, both in communication, social and behavioral aspects.